Investigation of Time-Dependent Microscale Close Contact Melting. (February 2021) - Aljaghtham, Mutabe; Premnath, Kannan; Alsulami, Radi
Highlights: Microscale close contact melting in the presence of a magnetic field is introduced An analytical solution for the thin film flow and energy transport coupled with unsteady phase change heat transfer is performed Navier slip conditions and their interactions with the electromagnetic fields specified via the Maxwell's equations is developed Numerical solution found that increasing the slip velocity in the absence of temperature slip increases the melting rate When temperature slip is included, increase in slip velocity leads to slower melting rate Abstract: Close-contact melting process occurs due to direct heating of phase change material (PCM) by a sliding heater plate. Due to the shearing motion, a squeeze film flow is developed between them, which generates the pressure needed to support the PCM. Such close-contact melting phenomena have numerous applications in engineering and natural settings. When a micro flow is developed in the squeeze film, for example in microelectromechanical systems (MEMS), slip effects in velocity and/or temperature can become significant. This study investigates the influence of slip velocity and/or temperature on the contact melting of an electrically conducting PCM in the presence of a magnetic field. An analytical solution for the thin film flow and energy transport coupled with unsteady phase change heat transfer under Navier slip conditions and their interactions with the electromagnetic fields specified via the Maxwell's equations is developed. Numerical solutions of the resulting model in non-dimensional form revealed the effect of various characteristic parameters on the transient variation of the melting rate and the liquid film thickness. In particular, it is found that increasing the slip velocity in the absence of temperature slip increases the melting rate, with an earlier onset of the steady state. More specifically, the melting rate increases by 24% and the film thickness decreases by 28 % when the dimensionless slip length for velocity λ ˜ equals to 1 × 10 −3 compared to the corresponding no slip case. On the other hand, when temperature slip is included, an increase in slip velocity leads to slower melting rate as well as taking longer to attain the steady state. The melting rate decreases 36 % and the film thickness increases by 39%, when the dimensionless slip length for temperature λ ˜ H equals to 1 × 10 −3 compared to corresponding no slip case.